2013
DOI: 10.2320/matertrans.m-m2013809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Accelerated Carbonation on the Leaching Behavior of Cr in Municipal Solid Waste Incinerator Bottom Ash and the Carbonation Kinetics

Abstract: The accelerated carbonation process with CO 2 absorption to confirm the leaching behavior of Cr in municipal-solid-waste incinerator (MSWI) bottom ash was investigated. This investigation was performed by placing samples in a CO 2 chamber. Only the temperature of the chamber at atmospheric pressure was varied and the CO 2 concentration was kept constant at 30% while the water-to-solid ratio was held at 0.3 dm 3 /kg. The result of an XRD analysis indicated that CO 2 could combine with portlandite, ettringite an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…10, we could confirm that Cr-fractions exist in the inner porous layer of Ca-Al compounds before carbonation reaction, but new and irregularly-shaped substances with CaCO 3 and amorphous Al 2 O 3 are wrapped around Cr-fractions after carbonation reaction. This provides evidence of the morphological changes in the particles in what is termed the encapsulation effect 21,22 .…”
Section: Carbonation Effect On Heavy Metal Stabilizationmentioning
confidence: 87%
“…10, we could confirm that Cr-fractions exist in the inner porous layer of Ca-Al compounds before carbonation reaction, but new and irregularly-shaped substances with CaCO 3 and amorphous Al 2 O 3 are wrapped around Cr-fractions after carbonation reaction. This provides evidence of the morphological changes in the particles in what is termed the encapsulation effect 21,22 .…”
Section: Carbonation Effect On Heavy Metal Stabilizationmentioning
confidence: 87%
“…This structure consists of columns of {Ca 6 and AsO 2À 4 . 21,22) However, the important phenomenon 23,24) is that heavy metal ions substituted into ettringite can be easily released from the particle surface to the outside because the ettringite is easily decomposed by carbonation with CO 2 . In addition, the occurrence of volume change due to the carbonation with CO 2 in the bottom ash can be also expected.…”
Section: Washing Treatmentmentioning
confidence: 99%
“…However, it couldn't reach 100% because of the existence of other insoluble chlorides except Friedel's salt, such as sodalite, which is not easily decomposed with CO 2 . According to the literatures, 23,24) the quench products are the main alkaline inorganic materials in the reaction with CO 2 . These carbonation reactions of Friedel's salt (eq.…”
Section: Accelerated Carbonation Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Um et al [75] subjected municipal solid waste incinerator bottom ash (MSWI-BA) with particle size < 150 µm to carbonation using 30 vol% CO 2 with 0.3 L/S at different temperatures (20-40 • C), for the purpose of studying the leaching behavior of Cr. XRD results showed that portlandite (Ca(OH) 2 ), ettringite (Ca 6 Al 2 (SO 4 ) 3 (OH) 12 ·26H 2 O) and hydrocalumite (Ca 8 Al 4 (OH) 12 (Cl,CO 3 ,OH) 2− ·4H 2 O) disappeared from the material's composition after carbonation experiments.…”
Section: Incineration Ashesmentioning
confidence: 99%